SELF CONTROL MAHASISWA PEREMPUAN PENGGUNA SMARTPHONE SERTA IMPLIKASINYA DALAM BIMBINGAN KONSELING ISLAM - Fadil Maiseptian; Rosdialena Rosdialena; Erna Dewita (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The high level of smartphone users by women today is certainly accompanied by the contribution of technology to support life processes, especially in learning. Therefore, a female student must be able to control herself in using a smartphone appropriately, so that inappropriate behavior does not occur. The purpose of this study was to describe the level of self-control of female students using smartphones based on aspects of behavior control, cognitive control, decision control. The method used in this research is quantitative. The measuring instrument used is a self-control instrument that has been tested for validity and reliability and is analyzed using a simple proportion formula. The result of this research is that self-control of female students from the aspects of behavior control, cognitive aspects, and decision control is still low. This is an important note for the campus to contribute to the environment for students in using smartphones. Based on this, Islamic guidance and counseling services are needed in higher education to be able to provide understanding to female students in smart and quality smartphone use. Therefore, a technical institution that focuses on providing Islamic guidance and counseling services in higher education is needed so that the appropriate behavior that arises due to weak self-control can be overcome